Implementation of public information disclosure policy in the house of Representatives of the Republic of Indonesia - Ferdaus, Feri; Zaimasuri, Zaimasuri (Journal of Governance and Accountability Studies, 2023)
Purpose: This study aims to identify how the implementation of the public information disclosure policy in the House of Representatives (DPR) in 2019-2021 is going and to find the right strategies to be implemented so that the DPR can become an informative public body. Research methodology: This research uses a qualitative descriptive method with a case study approach, where primary and secondary data are obtained through in-depth interviews with predetermined key informants, field observations, and literature studies relevant to the research topic. Results: The findings show that the implementation of public information disclosure policy in Parliament is still not optimal due to various obstacles in the process of documenting, classifying, managing, and serving public information that are technical, administrative, bureaucratic, and political in nature. DPR needs to start building and developing an internal big data system that is connected to real time public information management and service applications. In addition, the active role of Members and factions in the House in providing public information is also important to support the successful implementation of public information disclosure in the House.